Odpowiedzi

2010-02-04T21:45:22+01:00
A) 2x-7-[5x²-3x-(2-4x+x²)]= 2x-7-[5x²-3x-2+4x-x²]= 2x-7-5x²+3x+2-4x+x²=x-4x²-5
b) 3-x²-[2-2x²-(3x²-2x-1)]= 3-x²-[2-2x²-3x²+2x+1]=3-x²-2+2x²+3x²-2x-1= 4x²-2x
c) 4x+3-[x-3x²-(6-3x-x2)]= 4x+3-[x-3x²-6+3x+2x]= 4x+3-x+3x²+6-3x-2x= x+9+3x²
d) 3x²-5x-[x-3x-(2+4x-x²)]= 3x² -5x-[x-3x-2-4x+x²]= 3x²-5x-x+3x+2+4x-x²= 2x²+x+2
Najlepsza Odpowiedź!
2010-02-04T21:46:58+01:00
A) 2x-7-(5x²-3x-2+4x-x²)=2x-7-5x²+3x+2-4x+x²=x-4x²-5
b) 3-x²-(2-2x²-3x²+2x+1)=3-x²-2+2x²+3x²-2x-1=4x²-2x
c) 4x+3-(x-3x²-6+3x+2x)=4x+3-x+3x²+6-3x-2x=3x²-2x+9
d) 3x²-5x-(x-3x-2-4x+x²)=3x²-5x-x+3x+2+4x-x²=2x²+x+2
2010-02-04T22:22:24+01:00
A) 2x-7-[5x²-3x-(2-4x+x²)]=2x-7-(5x²-3x-2+4x-x²)=2x-7-5x²+3x+2-4x+x²=x-4x²-5

b) 3-x²-[2-2x²-(3x²-2x-1)]=3-x²-(2-2x²-3x²+2x+1)=3-x²-2+2x²+3x²-2x-1=4x²-2x

c) 4x+3-[x-3x²-(6-3x-x2)]=4x+3-(x-3x²-6+3x+2x)=4x+3-x+3x²+6-3x-2x=3x²-2x+9

d) 3x²-5x-[x-3x-(2+4x-x²)]=3x²-5x-(x-3x-2-4x+x²)=3x²-5x-x+3x+2+4x-x²=2x²+x+2